PENGGUNAAN PROGRAM PEMBELAJARAN MACROMEDIA FLASH PROFESSIONAL 8 PADA KERAJINAN KERAMIK UNTUK MENINGKATKAN DESAIN PRODUK - Muhammad Sholahudin AL Ghofari (SANGKAREANG, 2016)
This study aims to reveal differences of creativity level of products design of ceramic craft, between students who use the learning Macromedia Flash Professional 8 program and those who use the Microsoft Office Powerpoint program. This study was a quasi-experimental study. The dependent variable was the creativity of products design of ceramic craft of the sudents of craft. The independent variables were learning Macromedia Flash Professional 8 program and Microsoft Office Powerpoint program. The research design was quasi-experimental design. Research subjects were 22 students. The data collection instruments used were in the form of ceramic handicraft products assessment tests. The data were analyzed using analysis of independent Samples T-Test and Paired Samples T-Test, with at a significance level of 5% (α = 0.05). The results of this study indicate that, creativity of products design of ceramic craft who use the learning Macromedia Flash Professional 8 program is higher than that creativity of products design of ceramic craft who use the Microsoft Office Powerpoint program. Evidenced the are differences of creativity level of products design of ceramic craft of the Students of Craft who use the learning Macromedia Flash Professional 8 program, with the results of the analysis of Independent Samples T-Test and Paired Samples T-Test. The column Sig. shows the sig. (0.000) < α ( 0.05 ). Thus that, the use of learning Macromedia Flash Professional 8 can enhance the creativity of products design of ceramic craft of the students of craft.